ANALYSIS OF THE SRPMK STEEL STRUCTURE ZONE PANEL MODELING METHOD ON THE SIMULATION RESULTS OF THE COLLAPSE OF THE PANCA BUDI UNIVERSITY CAMPUS BUILDING DUE TO EARTHQUAKE VIBRATION - T Yuan Rasuna; Muhammad Zaki Chairuman; Syarbaini Lubis (Yayasan Sinergi Multidimensi Kreatif, 2025)
This study aims to analyze the panel zone modeling method of SRPMK steel structure (Small Moment Full Frame System) in the context of simulating the collapse of the Panca Budi Development University campus building due to earthquake vibrations. With the increasing frequency and intensity of earthquakes, it is important to understand the behavior of steel structures, especially in the part of the zone panel that serves as a transition between beams and columns. The safety of students while on campus is a critical issue, considering that they spend a significant amount of time in these buildings. This study uses structural analysis software to identify the response of buildings to various earthquake scenarios. The simulation results show that the SRPMK method can accurately predict the collapse behavior of the panel zone, identify weak points and provide guidance in design improvements to improve the resilience of the building. These findings are expected to serve as a reference for structural designers in designing safer and more earthquake-resistant buildings, as well as contributing to the development of better construction standards in Indonesia, in order to maintain the safety and comfort of students during the learning process on campus.